IAAF Sprint start research project: Is the 100 ms limit still valid? - Komi, P. V.; Ishikawa, M.; Salmi, J. (New Studies in Athletics, 2009)
The current false Start criterion used by the IAAF is based on an assumed minimum auditory reaction time. If an athlete moves sooner than 100 ms after the start signal, he/she is deemed to have false-started. The purpose of this study, which was commissioned by the IAAF, was to examine neuromuscular reaction to the auditory signal used in the Sprint start and to determine whether the WO ms limit is correct. Seven nationallevel Finnish Sprinters took part. A comprehensive approach was used to study force reaction on the blocks, the movements of the arms and the activation profiles of several muscles. The authors found great Variation in individual reaction times and confirmed previous reports of simple auditory reactions as fast as 80 ms. They recommend that the 100 ms limit be lowered to 80 or 85 ms and that the IAAF urgently examines possibilities for detecting false starts kinematically, so that judges' decisions are based on the first visible movement regardless of the body part This can be done with a System of high-speed cameras, which gives views of all the athletes on the start line. With such a System, it would be possible to change the start rule so that no false Starts are permitted.